Mechanisms of Carbon Sequestration in Highly Organic Ecosystems : Importance of Chemical Ecology - Adamczyk, Bartosz; Heinonsalo, Jussi; Simon, Judy (My University, 2020)
Organic matter decomposition plays a major role in the cycling of carbon (C) and nutrients in terrestrial ecosystems across the globe. Climate change accelerates the decomposition rate to potentially increase the release of greenhouse gases and further enhance global warming in the future. However, fractions of organic matter vary in turnover times and parts are stabilized in soils for longer time periods (C sequestration). Overall, a better understanding of the mechanisms underlying C sequestration is needed for the development of effective mitigation policies to reduce land‐based production of greenhouse gases. Known mechanisms of C sequestration include the recalcitrance of C input, interactions with soil minerals, aggregate formation, as well as its regulation via abiotic factors. In this Minireview, we discuss the mechanisms behind C sequestration including the recently emerging significance of biochemical interactions between organic matter inputs that lead to C stabilization.
Keywords: 570